Utilisation of staff clinic facility in a Northwest Nigeria hospital: emerging challenges for the National Health Insurance Scheme. Issue 1 (17th February 2016) - Michael, GC; Grema, BA; Yakubu, SO; Aliyu, I
Abstract : Background: The health status of workers and their families affects workplace productivity. The National Health Insurance Scheme (NHIS) objective of improving healthcare accessibility to Nigerians has increased service utilisation but may pose new challenges to existing facilities. This study was undertaken to describe the pattern of clinic utilisation, disease entities of subjects, use of the excused-duty certificate and identify points of delay. Methods: A prospective cross-sectional study of 352 subjects randomly selected over 6 weeks among patients attending the Aminu Kano Teaching Hospital Staff clinic. Results: Most subjects (307, 87.2%) had insurance and were predominantly (227, 64.5%) dependants. Most subjects (190, 55%) had used the clinic once to three times in the preceding 12 weeks and were predominantly (85, 24.2%) hospital attendants. Infectious disease (204, 58%) was the commonest reason for the clinical encounter. Their mean waiting and consultation times were 77.3 (SD ± 43) and 9.6 (SD ± 4.5) minutes respectively. Only 52 (14.8%) subjects were seen within 30 minutes of clinic arrival. Only a few subjects (3, 0.9%) had received an excuse-duty certificate in the preceding 12 weeks, mainly for malaria. Conclusion: High clinic utilisation and acute infectious disease burden are major challenges for the clinic, while prolonged clinic waiting time was suffered by clinic users. Prolonged waiting time may affect workplace availability and productivity. Proactive improvements in the causal factors for prolonged clinic waiting time may be required.